Analisis Program Pelatihan dan Pengembangan Terhadap Kinerja Karyawan PT. Garuda Utama Persada - Al-sahbani, Muhamad Dzaki; Siska, Elmira (Lembaga Pengembangan Kinerja Dosen, 2024)
PT. Garuda Utama Persada is a company that provides security and loss prevention services to clients in related fields, mining, offices, housing, airports, power plants, factories, hotels, restaurants, banks, hospitals, shopping centers, warehouses and high-rise buildings. The aim of this research is to analyze the influence of training and development programs on employee performance at PT. Garuda Utama Persada. The research was conducted for 3 months (April – June 2024). The data collection method was through interviews and questionnaires which were distributed to 105 respondents. The analysis method is quantitative statistics. Data analysis includes instrument quality tests consisting of validity and reliability tests, classical assumption tests, t tests and F tests. The results of this research show that the training program partially has a positive and significant effect on employee performance (t count 3.114 > t table 1.98350 and sig value 0.002 < 0.05). Partial development has a positive and significant effect on the performance of PT employees. Garuda Utama Persada (t count 3.992 > t table 1.98350 and 0.000 < 0.05). The implication of the results of this research is that providing good training and development programs will improve employee performance.